2015
DOI: 10.11604/pamj.2015.20.181.5470
|View full text |Cite
|
Sign up to set email alerts
|

Lupus érythémateux systémique induit par l’isoniazide: une complication rare à craindre

Abstract: Le lupus induit est défini comme un syndrome lupique généralement cutanéo-articulaire secondaire à une exposition continue à un traitement et qui disparaît après arrêt de celle-ci. Nous rapportons deux cas de lupus induit par l'isoniazide. Il s'agissait de deux femmes âgées respectivement de 30 et 35 ans. Elles présentaient un lupus induit par l'isoniazide après un et deux mois de traitement d'une tuberculose ganglionnaire. La maladie s'est manifestée par des signes articulaires, une éruption cutanée, une leuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
(14 reference statements)
1
1
0
Order By: Relevance
“…A literature review suggested that isoniazid was the culprit drug among those used to treat the present patient [5,13]. The clinical presentation and ANA profile for this case are also similar to those reported by Jguirim et al for a previous case of isoniazid-induced SLE [14]. A pharmacovigilance investigation suggested a probable causal relationship between this drug and the reaction in the present case.…”
Section: Discussionsupporting
confidence: 83%
“…A literature review suggested that isoniazid was the culprit drug among those used to treat the present patient [5,13]. The clinical presentation and ANA profile for this case are also similar to those reported by Jguirim et al for a previous case of isoniazid-induced SLE [14]. A pharmacovigilance investigation suggested a probable causal relationship between this drug and the reaction in the present case.…”
Section: Discussionsupporting
confidence: 83%
“…Jguirim et al reported two cases of isoniazid-induced lupus in young women; after three months of treatment to lymph node tuberculosis, one of them presented with polyarthralgia, a pruritic maculopapular rash in the photo-exposed regions and diffuse bald patches in the scalp; the other one presented with tenosynovitis in the right hand and arthritis in the left ankle after one month of exposure to isoniazid. Both had leukopenia and anemia [7].…”
Section: Discussionmentioning
confidence: 99%